Brave New World. - Huxley, Aldous, 1894-1963.; Longman ([S.l.] : Longman Pub Group, 1994)
Bernard Marx becomes a citizen in an utopian World-State where babies are born in laboratories, there is no violence, all citizens take drugs for depression, and contentment overrides the free will of the populace, and presents the social climate in 1958, and the threats against personal freedoms that seemed to be p.
recursers to the novel's empty civilization.
English.
Keywords: Collectivism -- Literary collections; Passivity (Psychology) -- Literary collections; Genetic engineering -- Fiction; Totalitarianism -- Fiction